How to achieve full prophylaxis in young boys with severe haemophilia A: different regimens and their effect on early bleeding and venous access. (13th January 2015) - Nijdam, A.; Kurnik, K.; Liesner, R.; Ljung, R.; Nolan, B.; Petrini, P.; Fischer, K.; the PedNet study group
Summary To facilitate early prophylaxis, step‐up regimens starting prophylaxis with infusions 1× week−1 were introduced. Choice of initial regimen may affect outcome. This study aims to classify initial prophylactic regimens and compare them on short‐term outcome. From the 'European Paediatric Network for Haemophilia Management' (PedNet) registry, patients with severe haemophilia A without inhibitors, born 2000–2012, receiving prophylaxis were included. Treatment centres were classified according to the initial frequency of prophylactic infusions and the age at reaching infusions ≥3× week−1. Bleeding, and central venous access device (CVAD) use were compared at age 4 years. In 21 centres with 363 patients, three regimens were identified: (i) start prophylaxis with ≥3× week−1 infusions before age three (full: 19% of centres, 18% of patients); (ii) start 1–2× week−1, increasing frequency as soon as possible (asap), reaching ≥3× week−1 before age three (43% of centres, 36% of patients); (iii) start 1–2× week−1, increasing frequency according to bleeding (phenotype), reaching ≥3× week−1 after age three (38% of centres, 46% of patients). Prophylaxis was started at median 1.2 years on the full and asap regimen vs 1.8 years on the phenotype regimen. Complete prevention of joint bleeds was most effective on the full regimen (32% full vs. 27% asap and 8% phenotype), though at the cost of using most CVADs (88% full vs. 34% asap and 22% phenotype). The three prophylaxis regimens identified had different effects on early bleeding and CVAD use. This classification provides the first step towards establishing the optimum prophylactic regimen.